97.1k views
4 votes
HELP PLZ I NEED THIS DONE ASAP

HELP PLZ I NEED THIS DONE ASAP-example-1

2 Answers

5 votes
  • Given, y = -2

  • {y}^(2) + 9y + 3 \\ = {( - 2)}^(2) + 9( - 2) + 3 \\ = 4 - 18 + 3 \\ = 7 - 18 \\ = - 11

Hope you could get an idea from here.

Doubt clarification - use comment section.

User Webbi
by
5.2k points
5 votes

Answer:

Explanation:

The answer would be -19

User Miroo
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.